Software-based Live Migration for Containerized RDMA - Liu, Xiaoyu; Shu, Ran; Xiong, Yongqiang; Ren, Fengyuan (Proceedings of the 8th Asia-Pacific Workshop on Networking, 2024)
Container live migration is critical to ensure services are not interrupted during host maintenance in data centers. On the other hand, RDMA containerization has attracted both academia and industry for years. However, live migration for containerized RDMA is not supported in today’s data centers. Although modifying RDMA NICs (RNICs) to be aware of live migration has been proposed for years, there is no sign of supporting it on commodity RNICs. This paper proposes MigrRDMA, a software-based RDMA live migration for containers, which does not rely on any extra hardware support. MigrRDMA provides a minimum virtualization layer inside the RDMA library loaded in applications, which achieves transparent switching to new RDMA communications. Unlike previous RDMA virtualization that provides sharing and isolation, MigrRDMA’s virtualization layer focuses on keeping the RDMA states on the migration source and destination the same from the perspective of applications. Our evaluation shows that MigrRDMA only adds 0.7 ∼ 12.1 ms downtime to migrate a container with live RDMA connections running at line rate. Besides, the MigrRDMA virtualization layer only adds 3% ∼ 9% overheads in the data path operations.